Co-producing Parks: How Can Communities be Involved in their Design, Management, and Programming? - Kelly, Madeleine. (Tufts University. Tisch Library., 2022)
Thesis (M.S.)--Tufts University, 2022.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisors: Julian Agyeman, and Christine Cousineau.; Keyword: Urban planning.